Pembelajaran Angklung untuk SLB Bagian B Tuna Rungu Menggunakan Colouring Score Berbasis Multimedia - Diana Effendi (Universitas Lancang Kuning, 2019)
The introduction of angklung music especially for deaf students is done by replacing numeric notes with various hand movements by the teacher. It takes two teachers to produce harmonious music with one teacher focusing on melody and the other teacher focusing on chords. However, hand movements are still limited to ordinary notes. The teacher's hand movements do not yet include the crescendo and decrescence notes. In addition, if one of the teachers is unable to attend, it cannot produce a harmonious music. To overcome this, multimedia-based angklung learning aids and android-based applications are made, where multimedia allows an angklung game to be carried out without the help of a trainer. So that it can replace the score that is usually designated by a trainer, it can be replaced with an animated color change (colouring score) when the angklung tone is played. In this study using the Development Research method, the procedures in this study are (1) determining the concept (concept), (2) Media Design (Design), (3) Material Collection (Material Collecting), (4) Manufacturing Process (Assembly) , and (5) (Testing) .In this study identified the needs of users (trainers and angklung players), designing application story boards that are used as a reference at the implementation stage.This learning activity does not replace the role of the trainer, but only as a media alternative in carrying out angklung training activities.